Electrospinning of hierarchical structure Nd10W22O81 nanowires as high performance lithium storage anode for rechargeable batteries. Issue 4 (March 2018) - Chen, Ziwei; Cheng, Xing; Long, Nengbing; Zhu, Haojie; Yu, Haoxiang; Ye, Wuquan; Zheng, Runtian; Shui, Miao; Shu, Jie
Abstract: In this work, hierarchical structure Nd10 W22 O81 nanowires are successfully prepared by a feasible electro-spinning technique followed by heat treatment. The structure, morphology and electrochemical characteristics of Nd10 W22 O81 nanowires are investigated and compared with Nd10 W22 O81 particles fabricated by a high temperature solid state reaction. It can be observed that Nd10 W22 O81 nanowires display a "nanoparticle-in-nanowire" architecture. For comparison, solid state formed Nd10 W22 O81 is composed of irregular microsized particles. This hierarchical architecture makes Nd10 W22 O81 nanowires have higher Li-storage capacity and better rate performance, contributing to the larger ion channels and shorter ion transportation pathways. In addition, an in-situ X-ray diffraction investigation is also operated to study the structural evolution and reaction mechanism during the charge/discharge process. All these evidences indicate that hierarchical structure Nd10 W22 O81 nanowires could be a potential high capacity anode material for rechargeable lithium-ion batteries.